2020
DOI: 10.4103/ija.ija_154_20
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of paediatric King Vision™ videolaryngoscope and Macintosh laryngoscope for elective tracheal intubation in children of age less than 1 year: A randomised clinical trial

Abstract: Background and Aims: Paediatric airway, because of its consistent anatomical differences from that of an adult, often encounters difficulty in aligning the line of sight with the laryngeal inlet during intubation. Paediatric videolaryngoscopes (VLs), by obviating the need for aligning the line of sight with the glottis, offer several advantages over direct laryngoscopy. Therefore, this study aimed to compare the recently introduced paediatric King Vision™ VL (KVL) and the direct laryngoscope with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 21 publications
(8 reference statements)
0
0
0
Order By: Relevance
“…However, in difficult airways, the VLs enabled a higher first-pass success rate than conventional laryngoscopy. Garcia-Marcinkiewicz et al, in a multicentre, parallel group, randomized controlled trial, concluded that the first-attempt success rate was improved with video laryngoscopy with a standard blade in comparison to direct laryngoscopy (18) . As our study sample size was small and only included non-difficult airways, the observed difference between the two devices' success rates was minor, so we could not reach statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…However, in difficult airways, the VLs enabled a higher first-pass success rate than conventional laryngoscopy. Garcia-Marcinkiewicz et al, in a multicentre, parallel group, randomized controlled trial, concluded that the first-attempt success rate was improved with video laryngoscopy with a standard blade in comparison to direct laryngoscopy (18) . As our study sample size was small and only included non-difficult airways, the observed difference between the two devices' success rates was minor, so we could not reach statistical significance.…”
Section: Discussionmentioning
confidence: 99%